2014
DOI: 10.1097/aog.0000000000000391
|View full text |Cite
|
Sign up to set email alerts
|

Endometrioid Adenocarcinoma in an Extrauterine Adenomyoma

Abstract: Stage 1 endometrioid adenocarcinoma with concurrent, noninvasive, focal involvement in an extrauterine adenomyoma represents a secondary site and does not alter disease stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…[ 42 ] Caecum, descending colon and mesocolon 39 Total hysterectomy with LSO, RSO for endometriosis Right lower quadrant pain USG,CT Ovarian endometriosis Colonoscopic and laparoscopic resection M, B, C 26 Ulm et al. [ 43 ] 3 cm, left round ligament 49 Metromenorrhagia CT inguinal adenopathy TAH with BSO and lymph node dissection M 27 Torres et al. [ 44 ] 4 cm, right broad ligament 58 Post menopausal bleeding USG,CT malignancy Total Robotic hysterectomy with bilateral salpingo- oophorectomy M 28 Sopha et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 42 ] Caecum, descending colon and mesocolon 39 Total hysterectomy with LSO, RSO for endometriosis Right lower quadrant pain USG,CT Ovarian endometriosis Colonoscopic and laparoscopic resection M, B, C 26 Ulm et al. [ 43 ] 3 cm, left round ligament 49 Metromenorrhagia CT inguinal adenopathy TAH with BSO and lymph node dissection M 27 Torres et al. [ 44 ] 4 cm, right broad ligament 58 Post menopausal bleeding USG,CT malignancy Total Robotic hysterectomy with bilateral salpingo- oophorectomy M 28 Sopha et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ulm et al. [ 43 ] reported focal endometrioid adenocarcinoma in extrauterine adenomyoma (round ligament) with concurrent stage 1 uterine endometrioid adenocarcinoma. Rahilly et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar lesions were described in the small intestine [101] and the nervous system [102]. Extrauterine adenomyomas may arise from the ovary [103], the ovarian ligament [104], the broad ligament [105] or the round ligament [106] and are not connected to the uterus. Rokitansky's early description may be an instance of an adenomyomatous polyp [21].…”
Section: Müllerianosis and Mixed Endometrial-myometrial Lesionsmentioning
confidence: 64%
“…Finally, it should point out for our that it seems no causal relationship existing between extrauterine adenomyoma of the lesser omentum and stomach adenocarcinoma. Previous reports have shown that extrauterine adenomyoma could also undergo malignant transformation, such as to endometrioid adenocarcinoma [7,24] or to clear cell carcinoma. [20,38] So far, there has been no report of the malignant transformation of extrauterine adenomyoma into endometrial stromal sarcoma and leiomyosarcoma, but it is possible in theory.…”
Section: Discussionmentioning
confidence: 99%